2008
DOI: 10.1073/pnas.0707920105
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of synaptic inhibition by phospho-dependent binding of the AP2 complex to a YECL motif in the GABA A receptor γ2 subunit

Abstract: The regulation of the number of ␥2-subunit-containing GABAA receptors (GABAARs) present at synapses is critical for correct synaptic inhibition and animal behavior. This regulation occurs, in part, by the controlled removal of receptors from the membrane in clathrin-coated vesicles, but it remains unclear how clathrin recruitment to surface ␥2-subunit-containing GABAARs is regulated. Here, we identify a ␥2-subunit-specific Yxx-type-binding motif for the clathrin adaptor protein, AP2, which is located within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 35 publications
(65 reference statements)
1
112
1
Order By: Relevance
“…There is possibly a switch of synaptic GABA A subunits in LTS cells from a majority of ␣2-containing receptors to ␣1 via a homeostatic up-regulation of ␣1 subunits (as noted by amplitude increases) or a down-regulation of ␣2 subunits (as noted by decay decreases). Although we show an increase in ␣1 function, data from the present study indicate that possible changes may involve alterations that do not involve changes in expression levels, such as phosphorylation (39). A major redistribution of ␣1 subunits from synaptic to extrasynaptic locations on the cell membrane appears unlikely, because we observed no significant changes in rise times (40).…”
Section: Long-term Sensory Deprivation Causes a Switch In Functional contrasting
confidence: 69%
“…There is possibly a switch of synaptic GABA A subunits in LTS cells from a majority of ␣2-containing receptors to ␣1 via a homeostatic up-regulation of ␣1 subunits (as noted by amplitude increases) or a down-regulation of ␣2 subunits (as noted by decay decreases). Although we show an increase in ␣1 function, data from the present study indicate that possible changes may involve alterations that do not involve changes in expression levels, such as phosphorylation (39). A major redistribution of ␣1 subunits from synaptic to extrasynaptic locations on the cell membrane appears unlikely, because we observed no significant changes in rise times (40).…”
Section: Long-term Sensory Deprivation Causes a Switch In Functional contrasting
confidence: 69%
“…Having established that lysosomal degradation of GABA A Rs is an important determinant of the number of surface and synaptic GABA A Rs, we next set out to identify the molecular mechanisms that mediate lysosomal targeting of GABA A Rs. Because the ␥2 subunit is an important determinant for the trafficking of GABA A Rs, and their entry into the endocytic pathway (22)(23)(24)(25), we examined the possible role that this subunit plays in receptor lysosomal targeting. We compared the lysosomal targeting in HEK-293 cells of GABA A Rs composed of ␣␤ and ␣␤␥2 subunits modified with N-terminal 9E10 reporters.…”
Section: Identification Of a Sorting Motif In The Gabaar ␥2 Subunit Thatmentioning
confidence: 99%
“…Recruitment of GABA A Rs into the endocytic pathway is facilitated via the interactions of the intracellular domains of receptor ␤1-3 and ␥2 subunits with 2-AP2 (7,11). In vitro studies identified the presence of a basic patch 2-AP2 binding motif between residues 401-412 for the ␤3 subunit (7) and showed that phosphorylation of S408/9 sites, the principal sites of phosphorylation for cAMPdependent protein kinase (PKA) and protein kinase C (1), inhibits binding of 2-AP2 to the ␤3 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…3A). mIPSCs were isolated by the inclusion of TTX, DAP5, and CNQX to block voltage-gated sodium channels, and glutamate receptors, respectively (4,11). Under these conditions, the remaining events were blocked by picrotoxin confirming that they arise via the activation of GABA A Rs (Fig.…”
Section: Mutation Of S408/9 Slows Endocytosis Of the ␤3 Subunit In Hementioning
confidence: 91%